Multiple primary malignant neoplasms of the mouth and oropharynx - M. A. Kropotov; L. P. Yakovleva; L. G. Zhukova; G. O. Agabekyan; A. V. Khodos; D. A. Safarov; P. A. Gavrishchuk; M. S. Tigrov; A. S. Vyalov (Опухоли головы и шеи, 2022)
Introduction. Probability of development of multiple primary tumors in patients who received treatment due to head and neck cancers varies between 5.6 and 35.9 % per different sources. moreover, treatment capabilities are severely limited by postoperative anatomical changes and previous radiation therapy, and the second tumor frequently causes death in these patients.The study objective is to identify the epidemiological features of the development of synchronous and metachronous primary multiple tumors in the head and neck.Materials and methods. The article analyzes data on 103 patients with multiple primary tumors who received treatment due to tumors of the head and neck between 1991 and 2020 at the N.N. Blokhin National medical Research Center of Oncology and A.S. Loginov Moscow Clinical Scientific Center.Results. During the study, typical locations of metachronous tumors in patients who received treatment due to primary malignant tumors of the head and neck were determined, duration of development of multiple primary tumors, treatment methods and survival rates were analyzed.Conclusion. Due to high risk of multiple primary tumors in patients who received treatment due to malignant tumors of the head and neck in the next 5 plus years, it is expedient to observe these patients during their whole lifetime. Considering typical locations of metachronous tumors, examination during dynamic observation should include instrumental methods such as panendoscopy. Surgical treatment should involve the whole spectrum of minimally invasive interventions including CO2 laser surgery and transoral robot-assisted interventions.